Preparation and Characterization of a Novel Cocrystal of Atorvastatin Calcium with Succinic Acid Coformer - Yudi Wicaksono; Dwi Setyawan; Siswandono Siswandono; Tri Agus Siswoyo (Universitas Gadjah Mada, 2019)
Preparation and characterization of a novel cocrystal of atorvastatin calcium with succinic acid coformer were successfully performed. This research aims to modify the crystalline form of atorvastatin calcium through cocrystallization with succinic acid coformer. The cocrystal was prepared by a solvent evaporation method and characterized by Powder X-Ray Diffraction (PXRD), Differential Scanning Calorimetry (DSC), Fourier Transform Infrared Spectroscopy (FTIR) and Scanning Electron Microscopy (SEM). The atorvastatin calcium-succinic acid cocrystal has new crystalline peaks at 2θ of 12.9, 18.2 and 26.7° indicating the formation of a new crystalline phase. The cocrystal showed the melting point at 205.7 °C with an enthalpy of fusion 30.2 J/g which is different from the initial components. The FTIR spectra of cocrystal showed the shifting of absorption peaks of groups of initial components indicating of formation of atorvastatin calcium-succinic acid cocrystal through acid–amide intermolecular hydrogen bond interactions. The solubility and dissolution test showed that the cocrystal has solubility and dissolution rate significantly higher than the solubility and dissolution rate of pure atorvastatin calcium.